2017
DOI: 10.1016/j.jocd.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Abnormal Fracture Healing as Detected With High-Resolution Peripheral Quantitative Computed Tomography

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Thus, we cannot currently state that the calculated stiffness parameters correspond to the actual biomechanical characteristics of the fracture region. Nevertheless, as our earlier studies have also shown, HR-pQCT and μFEA are able to assess both initial fracture features as well as changes during fracture healing with an association with functional outcome [9,12,22].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Thus, we cannot currently state that the calculated stiffness parameters correspond to the actual biomechanical characteristics of the fracture region. Nevertheless, as our earlier studies have also shown, HR-pQCT and μFEA are able to assess both initial fracture features as well as changes during fracture healing with an association with functional outcome [9,12,22].…”
Section: Discussionmentioning
confidence: 80%
“…The combined score ranges from 0 (no pain/disabilities) to 100 (worst pain/disabilities). PRWE results were clustered in categories according to severity as described elsewhere [16]: none/minimal (0−20), mild (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), moderate (41-60), severe (61-80) and very severe (81-100).…”
Section: Functional Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The effects of both AOMs on bone microarchitecture and strength were not investigated. These effects have been studied using HR-pQCT in postmenopausal women [76][77][78], but they cannot necessarily be extrapolated to GIOP due to differences in the pathophysiology of the bone loss between GIOP and postmenopausal osteoporosis [72]. Correspondingly, the effects of denosumab and risedronate on bone microarchitecture and strength in individuals on GC-treatment remain to be elucidated.…”
Section: Anti-osteoporosis Medication In Secondary Osteoporosismentioning
confidence: 99%
“…Additionally, guidelines should be developed for the quality grading of multi-stack scans, the exclusion of multi-stack scans from quantitative analyses based on their quality, and the correction of stack shifts. Besides that, the ability of HR-pQCT to early detect abnormal fracture healing or healing complications should be further explored [78]. Future fracture healing studies may consider using HR-pQCT (or other higher-resolution modalities).…”
Section: Distal Radius and Scaphoid Fracture Healingmentioning
confidence: 99%